2022
DOI: 10.21608/mid.2022.120290.1245
|View full text |Cite
|
Sign up to set email alerts
|

The seroprevalence trend of Helicobacter pylori infection in Gombe: A 5-year respective study

Abstract: Background: Helicobacter pylori (H. pylori) infection is highly prevalent globally and half of the world's population are carrying the pathogen with infection rates higher in low and middle-income countries. The study aim was to retrospectively determine the seroprevalence trend of H. pylori infection among patients suspected to have dyspepsia and identify socio-demographic determinants for H. pylori seropositivity. Methods: This retrospective study was conducted at the State Specialist Hospital, Gombe, Nigeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…This observation aligns with the findings ofZhu et al (2014), who found that H. pylori infection is more common in 30-to 39-year-olds. Our observation is even withAyodele et al (2018) andIbrahim et al (2022), who found that H. pylori infection is more common in the 31-to 40-year age group in Port Harcourt, and Lafia, respectively.The present observation with age disagrees with that ofAlubi et al (2023) who reported a higher prevalence in 20-40 years age groups in Port Harcourt, Nigeria. Additionally, it contradicts the findings ofEfere (2019) and Innocent-Adiele et al (2023), who found a higher frequency in the 26-30 age range.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…This observation aligns with the findings ofZhu et al (2014), who found that H. pylori infection is more common in 30-to 39-year-olds. Our observation is even withAyodele et al (2018) andIbrahim et al (2022), who found that H. pylori infection is more common in the 31-to 40-year age group in Port Harcourt, and Lafia, respectively.The present observation with age disagrees with that ofAlubi et al (2023) who reported a higher prevalence in 20-40 years age groups in Port Harcourt, Nigeria. Additionally, it contradicts the findings ofEfere (2019) and Innocent-Adiele et al (2023), who found a higher frequency in the 26-30 age range.…”
supporting
confidence: 72%
“…This observation aligns with the findings ofZhu et al (2014), who found that H. pylori infection is more common in 30-to 39-year-olds. Our observation is even withAyodele et al (2018) andIbrahim et al (2022), who found that pylori infection is more common in the 31-to 40-year age group in Port Harcourt, and Lafia, respectively.…”
supporting
confidence: 71%
See 1 more Smart Citation